Water and sustainable development - Schmitz, P. Michael (Frankfurt, 2005)
The Developing Countries Prize of the University of Gießen provokes aca demic contributions to the improvement of the living conditions in developing countries. This book is written to document the results of the interdisciplinary symposium Water and Sustainable Development which was held in October 2004. The water issue is one of the most urgent problems facing developing countries: 1.1 billion people still do not have access to safe water, and 2.4 billion lack access to basic sanitation. In spite of huge efforts during the past two decades, water is becoming increasingly scarce, and this in turn is causing disagreement and regional conflicts. According to recent estimates by the UN, if the world's population continues to grow at its current rate, by the year 2025 3.4 billion people won't have access to sufficient water. These people are facing major health problems and have much lower chances of developing. This book analyses the major problem, identifies the driving forces behind the water issue und discusses methods of solution.
Keywords: Water